Evaluasi Rasionalitas Penggunaan Obat Antihipertensi di Instalasi Rawat Jalan RSUD dr. Soegiri Lamongan Periode Tahun 2017 - Dian Sa'idah; Hajar Sugihantoro; Abdul Hakim; Siti Maimunah (Fakultas Farmasi Universitas Pancasila, 2019)
Hypertension is a non-communicable disease characterized by increased blood pressure that reaches > 140/90 mmHg. The incidence of hypertension and its complications continues to increase every year so the potential for irrational use of drugs is also increasing. The purpose of this study was to determine the rationality of the use of antihypertensive drugs at the outpatient installation of Hospital Dr. Soegiri Lamongan in the 2017 period, which reviews the exact indication, the right patient, the right drug, and the right dosage. This study is an observational study conducted by descriptive method and uses retrospective data, namely medical record sheets of hypertensive patients in 2017. The sampling method used was proportional stratified random sampling. The study population was 451 medical records of hypertensive patients, the number of samples used was 82 medical records where there were 269 prescription sheets in it. The data obtained are then compared using the 2013 American Society of Hypertension (ASH) literature and 2017 Hypertension Clinical Guidelines. The results showed that the rationality of the use of antihypertensive drugs in Dr. Soegiri Lamongan Hospital in 2017 period is 100% accurate on indications, 91,82 % right on patients, 88,85% right on drugs, and 98,14% right on dosages.